Typical Methodological Failures Demonstrated by Students of Teachers’ College in Conducting Classroom Action Research - Lalu Ari Irawan (Universitas Pendidikan Mandalika, 2018)
Conducting a research is a compulsory skill to be accomplished by any teacher students of English language teaching (ELT) department in teacher’s college. As a minimum requirement, each teacher-student must have experience to conduct a sophisticated Classroom Action Research (CAR). Within this skill, a teacher-student is expected to grasp various challenges that may occur in learning, therefore to take necessary actions in order to improve the quality of learning. Hence, this paper is composed due to an assumption occurred in a preliminary study that students in English language teaching department have demonstrated numbers of methodologically failures in conducting CARs. This assumption stimulates a question to answer further, “What sorts of methodologically failures are demonstrated by teacher’s college students in conducting CARs?” Researchers as the main instrument in this study develop theoretical criteria form based on prominent works of Susanto (2010), Hult and Lennung (1980), McKernan (1991), Kemmis and McTaggart (1992), Winter’s (1996), andMcNiff (2002) to frame the analysis. Data is taken from selected works stored in a library of a teacher’s college in Nusa Tenggara Barat, by employing two criteria to students’ works (mini-thesis), i.e. year of publication is 2015 and marked with ‘A’ from internal examination board of the college. These criteria constrain only two scripts to be further analyzed. By applying content analysis, this study reveals various kinds of methodological failure in students’ works about CAR, i.e. (1) violation to collaborative principle of CAR, (2) violation to the four characteristics of CAR (situational, participatory, evaluative, and cooperative), (3) the use of learners’ achievement as benchmark of success, (4) developed in quantitative study, (5) failure in positioning the researcher as a teacher or collaborator, and (6) failure in the construction of lesson plans.